Psychosocial Factors Affecting Self-Regulated Learning among Indonesian Islamic College Students: The Mediating Role of Perception Feedback - Diana Mutiah; Melisa Paulina; Muhammad Dwirifqi Kharisma Putra (Islamic Guidance and Counseling Journal, 2023)
In facing various problems during the online learning process, individuals need to have self-regulated learning to be able to undergo online lectures optimally and effectively. Hence, student’s knowledge increases, and learning objectives are achieved. This study aims to investigate the mediating effect of self-efficacy in the relationship between perception feedback on self-regulated learning in undergraduate students. Whether the mediation had varying effects on different age levels and sex differences was also examined. The sampling technique used in this study is non-probability sampling with 410 students. This study uses a quantitative approach with path analysis. In this study, researchers used confirmatory factor analysis (CFA) using Lisrel 8.8 to test the instrument's construct validity. The results showed a direct effect from the independent variables, namely self-efficacy, family support, and an indirect effect through mediator variables, namely self-efficacy, family support, friend support, and gender. The effect of self-efficacy and family support is partial mediation on self-regulated learning. In contrast, peer support and gender demographic variables have a perfect mediating effect on self-regulated learning with perception feedback as a mediator.